Finite element analysis of elastomeric bearings under compression and shear loading - Aynur, Mert Can. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Elastomeric bearings are widely used as isolators for buildings and bridges. Elastomeric bearings may be either stratified structures with repeated parallel layers of rubber and steel or plain rubber. This thesis focuses on computational approaches to evaluate global and local responses of plain rubber bearings and rubber-steel composite bearings which are subjected to either compression load or combination of compression and shear loads. During the development of the finite element model, accurate representation of the mechanical behavior of elastomer and steel, and geometric nonlinearities were addressed. Hyperelastic and viscoelastic material models for rubber were constructed using a set of test data available in the literature. The steel was represented with an elastoplastic material model. Using the developed finite element model, the effects of the rubber viscoelasticity, rubber compressibility and the bearing shape factor on the global response, i.e. vertical force, vertical stiffness, horizontal force, and horizontal stiffness, were studied in static analysis. In addition, the effects of magnitude of the applied load and friction on the local response of the bearing were studied in static analysis. For quasi-static analysis, the effects of the applied loading rate and compressibility of rubber on the predictions were determined. Implicit time integration for static analysis and explicit time integration for quasi-static analysis were used. The computational approaches presented in this thesis may be applied to the analysis of most isolators for buildings and bridges. Future studies may take into account cyclic shear loads along with compression load.
Keywords: Elastomers.; Bridges -- Earthquake effects.